Feline Paradise / Sallehuddin Noor Mohd. Salleh ... [et al.] - Mohd Salleh, Sallehuddin Noor; Tuyun, Roslan; Sabbas, Magdalena; Mat, Marlyna; Rambli, Siti Nasiha (2009)
We are starting our own business as partners, and all of us decided to call our business as Feline Paradise. Our main activity of business is providing service for cat grooming and followed by selling cat products. There are several departments in our business which are administrative department, operational department, marketing department and financial department. Each of us heads the department while one person acts as the General Manager, which heads all the departments in our business. We started this business with initial capital of RM 300,000.00 which contributed equally by partners (RM60,000.00 per partner) without getting loans from bank. Our office located in Alamesra, Kota Kinabalu, Sabah. There are reasons for us for choosing Alamesra as our office. One of the reason is Alamesra has not been fully developed. We took the chance before there are no chances left, to open a business in a develop area.